Seroprevalence and pathology of naturally infected Salmonellosis in poultry with isolation and identification of causal agents - Ahmed, AKM; Islam, MT; Haider, MG; Hossain, MM (Journal of the Bangladesh Agricultural University, 2010)
The present study was conducted to determine the seroprevalence of Salmonella infections in poultry. This study covered cultural prevalence with isolation and identification of the causal agent and pathological lesions in different organs produced by Salmonella in layer farms of Mymensingh district during July-December 2007. The materials were blood samples, liver and cloacal swabs from live and dead birds. The used methods were whole blood agglutination test by commercially available Salmonella antigen kit, culture in different media, Gram's staining, motility test, basic 5 sugar fermentation test and histopathology. The overall seroprevalence was 45.9% in live bird and the rate of seroprevalence decreased with advancement of age of birds. The cultural prevalence in seropositive group was 71% and in seronegative group was 59%. In dead bird, the cultural prevalence in liver was 64% and from cloaca 57%. A total 160 isolates were characterized, among them 64.2% were Salmonella Pullorum, 22.3% were Salmonella Gallinarum and 13.5% were Paratyphoid group of Salmonellae. Pathologically friable, bronze color liver with focal necrosis, various grades of enteritis, and hemorrhagic and congested egg follicles with stalk formation were found. Microscopically, focal necrosis and degeneration with leukocytic infiltration in liver, inflammatory cells in the mucosa and submucosa of intestine were found. In egg follicles, congestion and hemorrhages with leukocytic infiltration were found. The isolated Salmonella organisms may be used for further research such as serotyping, vaccine production and antibiotic sensitivity test. Keywords: Salmonellosis; Seroprevalence; Agglutination test; Histopathology; Poultry DOI: 10.3329/jbau.v6i2.4830 J. Bangladesh Agril. Univ. 6(2): 327-334, 2008